Biocerâmica de fosfato de cálcio nano-estruturado micro-macro porosa em grânulos de absorção rápida no preenchimento de defeito crítico em radio de coelhos (Oryctolagus cuniculus) - Jessica Alejandra Castro Varon (2013)
The objective of this study was to evaluate by radiography , histology and bone densitometry the effect of HA / TCP granules for rapid absorption in critical bone defect in radio rabbits ( Oryctolagus cuniculus ) . 35 rabbits were used in which a critical defect was performed on left and right radios . The animals were divided into GI , GII autograft and HA / TCP granules for rapid absorption . Radiographic examinations were made before surgery, immediately after the eighth , 15, 30 , 45, 60 , 90 and 120 days. At the end of each period, the animals were euthanized by anesthetic overdose and radios were harvested for histological assessment and densitometry . There was a significant difference between the treated and control groups when comparing bone mineral density obtained over the entire study period . It was verified histologically formation of a vascular network of the pores of bioceramic from the first time rating (eight days). Formation of primary bone tissue and trabeculae from preexisting bone tissue , were identified from the 30 days after implantation . At 60 days , the last time histological evaluation , we observed the presence of bone matrix from preexisting bone segments , featuring the centripetal bone formation . The bioceramic calcium phosphate nano - structured micro - macro porous granules for rapid absorption allows cell proliferation and invasion and thus promotes bone regeneration , thus becoming a suitable implant for filling bone defects criticism